2019
DOI: 10.22146/mgi.35570
|View full text |Cite
|
Sign up to set email alerts
|

Hidrogeomorfologi Dan Potensi Mataair Lereng Baratdaya Gunung Merbabu

Abstract: Karakteristik bentanglahan pada suatu wilayah merupakan salah satu faktor yang mempengaruhi distribusi spasial mataair. Penelitian ini dilaksanakan pada lereng baratdaya Gunung Merbabu dengan tujuan: (1) menganalisis persebaran mataair berdasarkan satuan bentuklahan, (2) menganalisis jenis mataair serta kualitas dan kuantitas air. Untuk mencapai tujuan tersebut digunakan metode survei dengan pengambilan sampel secara sistematik. Analisis data dilakukan secara deskriptif dengan memperhatikan aspek spasial diduk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 2 publications
2
8
2
Order By: Relevance
“…The water discharge varies with a fairly large range in both Sumbing and Sindoro is the same as the findings from Aurita and Purwantara [3], Sudarmadji et al [28], and Ashari and Widodo [1]. This indicates that in the Sumbing and Sindoro aquifer systems, certain zonescan drain large amounts of groundwater, resulting in the emergence of springs whose discharge is also large.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The water discharge varies with a fairly large range in both Sumbing and Sindoro is the same as the findings from Aurita and Purwantara [3], Sudarmadji et al [28], and Ashari and Widodo [1]. This indicates that in the Sumbing and Sindoro aquifer systems, certain zonescan drain large amounts of groundwater, resulting in the emergence of springs whose discharge is also large.…”
Section: Discussionsupporting
confidence: 85%
“…Judging from the difference with air temperature, all non-existent springs are hot springs [23], however, most were included in the hypothermic zoning [29]. The findings, which show that most of the water temperature is lower than the air temperature, is the same as previous research conducted in stratovolcano landscapes, including the Merbabu Volcano [1], Merapi Volcano [2], [3], and Ciremai Volcano [29]. Regarding this phenomenon, \ [5]based on Santoso's research in Lawu Volcano, it also showed that depressive springs such as those found in Sumbing and Sindoro were mostly hypothermal in natur.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations